Preventing and managing pharyngocutaneous fistula after total laryngectomy - A narrative review - Piazza, Cesare; Montenegro, Claudia; Vander Poorten, Vincent (Frontiers in Oncology, 2025)
Pharyngocutaneous fistula (PCF) remains one of the most frequent and serious complications following total laryngectomy (TL). PCF can lead to severe health issues such as infections and thromboembolic events prolonging hospitalization, as well as to life-threatening large neck vessels blowout and mediastinitis. Despite technical advancements, PCF rate after TL remains around 10%, underlining its challenges in terms of prevention and management. Numerous studies have identified risk factors contributing to PCF development: they can be distinguished into patient-, tumor-, and surgical technique related variables. Nevertheless, a wide consensus has yet to be reached for most of them. Two of the most encountered and recognized risk factors are certainly represented by salvage setting after failure of (C)RT and extension of TL to oro-, hypopharynx or cervical esophagus. In the first scenario, the use of both pedicled and free flaps either with an onlay or an inlay technique have been described, while in case of extended TL, general consensus has been reached in favor of inlay free flaps. Simultaneous use of salivary bypass tube is another commonly applied tool for PCF prevention. This review aims to describe current strategies for prevention and management of PCF after primary and salvage TL with possible extension to adjacent sites.